Penggemar K-Pop sebagai Digital Author dalam Menulis Fan Fiction di Twitter - Mardiyanti, Rizka Ainul; Kusuma, Ade (LPPM Institut Nasional Laa Roiba Bogor, 2024)
The development of technology in this globalization era has led to the creation of digital fandom. Along with the presence of fandom, it is balanced with the development of forms of support from fans for their idols, one of which is fan fiction. The creation of fan fiction itself has various stages and processes, before finally being uploaded for readers to enjoy. Most writers in the fan fiction genre started as fans. This research uses a qualitative approach and descriptive research type. The determination of informants was carried out using purposive sampling technique. To assist the research, in-depth interviews were conducted by reviewing fan culture in fan studies. Documentation and in-depth interviews were supplemented with various literatures to strengthen the research. The results show that text production is the author's activity in creating fan fiction works. In producing the text, the author performs various stages starting from the visualization stage, creative process, writing process, and editing & posting process. The author's purpose in writing fan fiction is because the author has ideas related to boy band Seventeen that they want to pour in the form of fan fiction. Keywords: Text production, fans, K-Pop, fan fiction